Penerapan Model PBL Dalam Pembelajaran Matematika Materi Bangun Datar Segi Empat Dan Segitiga - Millenia Cruisita Lukas; James U.L. Mangobi; Murni Sulistianingsih (Journal on Education, 2024)
Application of the PBL Model in Mathematics Learning Material on Rectangular and Triangular Figures. Mathematics Department. Faculty of Mathematics, Natural and Earth Sciences. Manado State University. Tondano 2024. Thesis. This research examines the differences in the learning outcomes of rectangular and triangular shapes for students who received the Problem-Based Learning model treatment and those who received the Direct Instruction model treatment at SMP Negeri 2 Tondano. The method used is quasi-experimental. The research design used was Posttest-only Control Group Design. The research subjects were 15 class VII-C students who received the PBL model treatment and 15 class VII-D students who received the DI model treatment. From this research, data was obtained in the form of learning results, and normality tests and homogeneity tests were carried out before hypothesis testing. The results of the normality test in the experimental class were obtained Lcount = 0.1475 < Ltabel = 0.2200, so the learning result data for the experimental class was normally distributed. Meanwhile, the normality test results in the control class were obtained Lcount = 0.0924 < Ltable = 0.2200, so the control class learning outcomes data were normally distributed. The homogeneity test results obtained Fcount = 1.0457 < Ftable = 2.4837, so the variance of the two classes is homogeneous. The results of hypothesis testing with a real level of α=0.05 obtained tcount = 1.8125 > ttable = 1.7011. Thus, it can be concluded that the average learning outcomes of students who received the PBL model treatment were higher than those of students who received the DI model treatment.